2013
DOI: 10.1074/jbc.m112.447771
|View full text |Cite
|
Sign up to set email alerts
|

LINGO-1 Receptor Promotes Neuronal Apoptosis by Inhibiting WNK3 Kinase Activity

Abstract: Background: Although antagonism of LINGO-1 is known to improve neuronal survival after injury, the mechanism is unknown. Results: LINGO-1 interacts with and inhibits WNK3 kinase activity, thereby facilitating neuronal apoptosis. Conclusion: LINGO-1 potentiates neuronal apoptosis, likely by inhibiting WNK3 kinase activity. Significance: Learning how LINGO-1/WNK3 signaling regulates neuronal survival is crucial for understanding the pathology of neurodegenerative diseases and injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Mi et al (2007) showed that the OPC maturation and remyelination are significantly enhanced in vitro and in vivo by inhibiting LINGO-1 function using dominant-negative LINGO-1, LINGO-1 RNAi, or LINGO-1-Fc but the specific protein that mediated the inhibition signal transduction was not described. Though our previous work has suggested that WNK1 and WNK3 are the downstream signaling molecules of LINGO-1 in neurons (Zhang et al, , 2013, little is known about their function in oligodendrocytes. In the present study, we showed that WNK1 and LINGO-1 were highly expressed in the cultured oligodendrocytes and interact with each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mi et al (2007) showed that the OPC maturation and remyelination are significantly enhanced in vitro and in vivo by inhibiting LINGO-1 function using dominant-negative LINGO-1, LINGO-1 RNAi, or LINGO-1-Fc but the specific protein that mediated the inhibition signal transduction was not described. Though our previous work has suggested that WNK1 and WNK3 are the downstream signaling molecules of LINGO-1 in neurons (Zhang et al, , 2013, little is known about their function in oligodendrocytes. In the present study, we showed that WNK1 and LINGO-1 were highly expressed in the cultured oligodendrocytes and interact with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysates were prepared as described previously (Zhang et al, 2013) and clarified by centrifugation at 11,200 g for 20 min at 4°C. An equal amount (300-500 μl) of supernatants was incubated with 5 μl of the corresponding antibodies for 2 h at 4°C.…”
Section: Immunoprecipitation and Immunoblottingmentioning
confidence: 99%
“…Since LINGO‐1 expression is upregulated after activation of the Trks receptors, LINGO‐1 may function in a negative feedback loop contributing to the homeostatic regulation of neurotrophin signaling. Moreover, the LINGO‐1 intracellular domain interacts with the Myt1 transcription factor 5 as well as members of serine threonine kinases including WNK1 and WNK3, which are, respectively, involved in LINGO‐1‐mediated inhibition of neurite extension 24 and neuronal apoptosis 25 …”
Section: Introductionmentioning
confidence: 99%
“…Because LINGO-1 is implicated in potentiating neuronal apoptosis under serum-deprivation conditions, 18,[27][28][29] and the LINGO-1 receptor complex can be activated by its agonist Nogo-66 28 or by self-interaction in trans, 30 were observed when serum-deprivation cultures were treated with LINGO-1 without or with the SP1 shRNA ( Figure 2C,D). In addition, the LINGO-1 expression was found decreased after SP1 inhibition (Figure 2E).…”
Section: Regulation Of Lingo-1 Expression By Sp1 and Inhibition Of mentioning
confidence: 99%
“…12 In addition, LINGO-1 antagonists have neuroprotective effects against injury-induced apoptosis in cultured neurons. 12,17,18 We previously reported that in an optic nerve crush (ONC) model, inhibition of LINGO-1 by RNA interference promoted regeneration of the optic nerve and the survival of RGCs. 19 Although inhibition of LINGO-1 promotes the survival of neurons and RGCs, the underlying mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%